2016
DOI: 10.1111/1471-3802.12240
|View full text |Cite
|
Sign up to set email alerts
|

School Participation of Students With Autism Spectrum Disorders

Abstract: This paper addresses the participation of students with autism spectrum disorders (ASD) in mainstream schools. There are different benefits for ASD students to be educated in an inclusive environment (Gena, 2006; Whitaker, 2004). They challenge the school community by presenting difficulties in essential domains for school activities (Chamberlain, Kasari and Rotheram‐Fuller, 2006; Eman and Farrell, 2009; Humphrey and Symes, 2010). Thus, these are students with increased difficulties participating in inclusive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Teixeira De Matos and Morgado ( 2016 ) reported that inclusion in mainstream schools is influenced by a positive attitude towards pupils with ASD and their behavior, their attendance in the school or class, and their overall acceptance in groups of typical developing pupils. Carter et al ( 2014 ) reported a high level of satisfaction with special solutions among both parents and teachers, as well as regular classroom placement for children with ASD.…”
Section: Previous Research On Pupils With Asdmentioning
confidence: 99%
“…Teixeira De Matos and Morgado ( 2016 ) reported that inclusion in mainstream schools is influenced by a positive attitude towards pupils with ASD and their behavior, their attendance in the school or class, and their overall acceptance in groups of typical developing pupils. Carter et al ( 2014 ) reported a high level of satisfaction with special solutions among both parents and teachers, as well as regular classroom placement for children with ASD.…”
Section: Previous Research On Pupils With Asdmentioning
confidence: 99%